Threat modeling: a study on its application in digital transformation from the perspective of risk - Junior , Abinel Santiago Cerqueira (2023)
Information security is a topic that has been increasingly discussed nowadays after the beginning of the pandemic and its understanding has been fundamental to protect information in several organizations. The present study aims to identify and analyze the application of threat modeling in digital transformation from the perspective of information security risks. For the development of the research, a systematic review of the literature was conducted with the adoption of a protocol based on PRISMA-P to identify which threat modeling techniques have been applied in digital transformation and which information security risk approaches are used in the application of the threat modeling. The result of this study suggests that threat modeling applied in digital transformation uses customized models by means of unspecified techniques and that qualitative risk approaches have been adopted more frequently in digital transformation.